A) -25 × 3s-4 nad 5=
b)16t × 5-2t nad 8 =
c) 3(-a +4) -½ (6-a)=
d) -1,1(2b-5) + 0,8(2- 0,3b)=
e) 15× 2y-5 nad 3 -8 × 3-7y nad 4=
f) 6s-5 nad 2 + -2s +7 nad 6=
g) (0,2c-0,1)(0,2c+0,1)=
h) 8(¼α-2)²=
i) - jedna dwunasta (4y+3)²
j) 0,2(2z-5)(2z+5)=
k) -(3b-2)² +(16b)²=
l) (5c-4)² +(5c-4)(5c+4)=


m)-0,2√6 nad 2√6 -5=
n)3-√2 nad 1+√2=
o) √7+√3 nad √3-√7=

1

Odpowiedzi

2009-09-23T06:51:32+02:00
A) -25 × 3s-4 nad 5=-75s-4 nad 5= 75s:1=75s
b)16t × 5-2t nad 8 =80t-2 nad 8= 80t:4=20t
c) 3(-a +4) -½ (6-a)=-3a+12-(3+½)= 3½a+9
d) -1,1(2b-5) + 0,8(2- 0,3b)=-2,2b+5,5+1,6-2,4b=-4,6b+7,1

przepraszam ze iwecej nie rozwiazalam ale usze wychodzic do szkoly; /